2022
DOI: 10.1007/s00420-022-01853-9
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for shoulder disorders among French workers: prospective cohort study

Abstract: Objectives Shoulder disorders are common in the working population. This longitudinal study aimed to explore the relationships between personal factors and occupational organisational, psychosocial, and biomechanical factors and the incidence of shoulder disorders. Methods A total of 3710 workers in the Pays de la Loire region (Loire Valley area, France) were randomly included by their occupational physician in the Cosali cohort between 2002 and 2005. All … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Work organization characteristics have effect on the biomechanical and psychosocial features of the working situations which workers encounter (25). Previous findings suggest indirect impacts of factors related to work organization on the risk of UEMSD (14,15,25,31), it is a possible explanation of the lower weights assigned to organizational predictors in the scoring system. But, organizational factors are understudied in the epidemiological literature compared to the ergonomic literature (25,34).…”
Section: Work-related Predictors In the Risk Scorementioning
confidence: 98%
See 2 more Smart Citations
“…Work organization characteristics have effect on the biomechanical and psychosocial features of the working situations which workers encounter (25). Previous findings suggest indirect impacts of factors related to work organization on the risk of UEMSD (14,15,25,31), it is a possible explanation of the lower weights assigned to organizational predictors in the scoring system. But, organizational factors are understudied in the epidemiological literature compared to the ergonomic literature (25,34).…”
Section: Work-related Predictors In the Risk Scorementioning
confidence: 98%
“…In addition to age and gender, a set of 47 occupational risk factors were selected as potential predictors of UEMSD (supplementary material, www.sjweh.fi/ article/4119, table S1) using background knowledge, literature reviews (3) and previous results on the Cosali Cohort (5,11,12,14,15). Individual data on these occupational factors were collected through a selfadministered questionnaire at baseline, completed by workers before their clinical OP examination.…”
Section: Candidate Predictorsmentioning
confidence: 99%
See 1 more Smart Citation
“…During this process, different individual factors play roles, of them, gender is important and worth further investigation from clinical and biomechanical aspects. At the first level, epidemiological studies have demonstrated that shoulder pain is more frequent in women than men [ 11 , 12 ]. This higher risk of shoulder pain in women have been attributed to different anthropometrical, biomechanical and motor control-related differences that could affect motor behaviors [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%